Diurnal regulation of VOCs may not be effective in controlling ozone pollution in China. (1st July 2021) - Wu, Weiling; Xue, Wenbo; Zheng, Yixuan; Wang, Yanli; Lei, Yu; Wang, Jinnan
Abstract: Over the past few years, marked increases in ground-level ozone (O3 ) concentration has been detected over much of eastern China. These high levels of O3 pollution have been demonstrated to be detrimental to human health and plant growth, which requires urgent control on China's O3 pollution. Among the various control measures, diurnal regulations of VOCs were adopted in some regions in China. For example, several local governments encourage factories with notable VOCs emissions shift their manufacturing processes to the nighttime; some governments also offer discount for night refueling. However, the effects of this diurnal regulation approach are still unclear. To evaluate the effectiveness of this measure, we proposed a quantitative assessment using WRF-CAMx air quality model. The assessment was systematically implemented at multiple time and spatial scales. Results at the regional scale revealed that the diurnal regulation of VOCs could slightly redistribute hourly O3 concentrations and had minor influence on hourly peak O3 concentration. The effects of this measure on hourly O3 concentrations varied substantially across different cities: positive or negative impacts on O3 concentrations were both found at the city level. At the daily scale, the variations of maximum daily 8-h average (MDA8) O3 concentrations were distributed between −1% and 1%, accounting for about 88%, 76%, 65% of the entire days in key regions under S1, S2, S3; the average O3 -polluted days demonstrated an increasing trend in "2 + 26″cities and YRD, but for FWP and PRD, there were little changes in average number of O3 -polluted days. And at the monthly scale, the effects were not satisfactory, monthly average MDA8 O3 demonstrated an increasing trend under VOCs regulation scenarios in "2 + 26" cities, FWP and YRD; Increasing or decreasing trends in monthly average MDA8 O3 were both found at the city level, but most of the variations were less than 1%. In general, Diurnal regulation of VOCs may not be effective in controlling ozone pollution at the regional scale. Measures proposed to control O3 pollution need more refined management and scientific evaluation before wide implementation. Highlights: VOCs diurnal regulation may not be effective in controlling O3 at the regional scale. VOCs diurnal regulation had minor influence on hourly peak O3 concentration. Positive or negative impacts on O3 concentrations were both found at the city level.